Die Dynamik des im Werden begriffenen Volkes Abrahams unter Isaak und Jakob in Gen 25-50 - Volgger, David (Liber annuus, 2022)
The present study demonstrates that five criteria are central to the texts on Isaac and Jacob in Gen 25-50. As in the previous analysis of Gen 12-25, so also in Gen 25-50 will I assume and argue that three relatively independent sources are the basis of its textual composition. Furthermore, textual analysis will reveal that sections such as Gen 24 (and the related 26:2-5 and 46:2-5); perhaps 27; * 29-33; 36 and Gen 37; (38); 39-45 (the "tale of Joseph") all show a deeper knowledge of the other sources and a higher level of literary treatment. In these cases, one could also speak of second-degree sources. Since all "sources" correspond to the five criteria and are similar in content presentation and systematic exposition, it is reasonable to assume a similar social environment and a similar era for their genesis.